2022
DOI: 10.1371/journal.pone.0279746
|View full text |Cite
|
Sign up to set email alerts
|

The role of activated androgen receptor in cofilin phospho-regulation depends on the molecular subtype of TNBC cell line and actin assembly dynamics

Abstract: Triple negative breast cancer (TNBC) is highly metastatic and of poor prognosis. Metastasis involves coordinated actin filament dynamics mediated by cofilin and associated proteins. Activated androgen receptor (AR) is believed to contribute to TNBC tumorigenesis. Our current work studied roles of activated AR and cofilin phospho-regulation during migration of three AR+ TNBC cell lines to determine if altered cofilin regulation can explain their migratory differences. Untreated or AR agonist-treated BT549, MDA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The role of AR in metastasis development includes coordinated actin filament dynamics mediated by cofilin and other connected proteins. Additional in vitro data showed that androgens enhanced cell polarization, stimulated wound healing and transwell migration rates and increased N/E-cadherin mRNA ratios [ 39 ]. Other evidence suggests that the AR might be a tumor suppressor in ERα -positive (BC, but a tumor promoter in ERα negative BC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of AR in metastasis development includes coordinated actin filament dynamics mediated by cofilin and other connected proteins. Additional in vitro data showed that androgens enhanced cell polarization, stimulated wound healing and transwell migration rates and increased N/E-cadherin mRNA ratios [ 39 ]. Other evidence suggests that the AR might be a tumor suppressor in ERα -positive (BC, but a tumor promoter in ERα negative BC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Control, 3 b ‐treated HCT‐116 cells, and 6 e ‐treated HeLa cells were lysed with the lysis buffer after 72 h of treatment [37] . Cell lysates were then boiled in a water bath and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…Control, 3 b-treated HCT-116 cells, and 6 e-treated HeLa cells were lysed with the lysis buffer after 72 h of treatment. [37] Cell lysates were then boiled in a water bath and sonicated. For immunoblotting, equal quantities of protein from control and treated cells were separated using 10 % SDS-PAGE and blotted onto nitrocellulose membrane.…”
Section: Immunoblottingmentioning
confidence: 99%